2012
DOI: 10.1371/journal.pone.0036746
|View full text |Cite
|
Sign up to set email alerts
|

Geminivirus-Mediated Delivery of Florigen Promotes Determinate Growth in Aerial Organs and Uncouples Flowering from Photoperiod in Cotton

Abstract: BackgroundPlant architecture and the timing and distribution of reproductive structures are fundamental agronomic traits shaped by patterns of determinate and indeterminate growth. Florigen, encoded by FLOWERING LOCUS T (FT) in Arabidopsis and SINGLE FLOWER TRUSS (SFT) in tomato, acts as a general growth hormone, advancing determinate growth. Domestication of upland cotton (Gossypium hirsutum) converted it from a lanky photoperiodic perennial to a highly inbred, compact day-neutral plant that is managed as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 52 publications
2
52
0
Order By: Relevance
“…In both cases, the F1 progeny displayed phenotypes intermediate to both parents, demonstrating the success of the cross. Importantly, neither dCLCrV nor ALSV was detected in the F1 generation McGarry and Ayre, 2012b).…”
Section: Virus-induced Flowering: Efficient Transient Induction Of Flmentioning
confidence: 85%
See 2 more Smart Citations
“…In both cases, the F1 progeny displayed phenotypes intermediate to both parents, demonstrating the success of the cross. Importantly, neither dCLCrV nor ALSV was detected in the F1 generation McGarry and Ayre, 2012b).…”
Section: Virus-induced Flowering: Efficient Transient Induction Of Flmentioning
confidence: 85%
“…This early work demonstrated that FT encoded florigenic properties and laid the foundation for VIF as a breeding tool. Work in cotton demonstrated that ectopic expression of AtFT from a disarmed Cotton leaf crumple virus (dCLCrV) vector uncoupled flowering from photoperiod, accelerated the transition to reproductive growth, and enhanced determinate plant architecture (McGarry and Ayre, 2012b). Ectopic expression of AtFT in soybean (Glycine max) with both determinate or indeterminate stem habits, when delivered by Apple latent spherical virus (ALSV), terminated vegetative growth without an inductive short-day treatment .…”
Section: Virus-induced Flowering: Efficient Transient Induction Of Flmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants respond to such biotic stresses by speeding up their reproductive process to flower earlier. This could complicate the interpretation of results of VIFs, such as those based on Zucchini yellow mosaic virus, Cotton leaf crumple virus, or Citrus leaf blotch virus, because all these viruses produced severe systemic symptoms in viral-infected plants (Lin et al, 2007;McGarry and Ayre, 2012;Velázquez et al, 2016). However, the PVX-infected tobacco plants exhibited normal vegetative and reproductive growth (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These findings open up possibilities for further development and application of the virus-induced flowering (VIF) assay in plants (McGarry et al, 2017). Since then, several RNA and DNA viruses, including Apple latent spherical virus, Cotton leaf crumple virus, and Citrus leaf blotch virus, have been engineered to express FT for floral induction in soybean, apple, pear, gentian, and lisianthus plants Yamagishi et al, , 2014Yamagishi et al, , 2016Fekih et al, 2016), cotton (McGarry andAyre, 2012;McGarry et al, 2016), and citrus (Velázquez et al, 2016). These latest developments have generated broad interest in the application of VIF for the benefit of crop breeding (McGarry et al, 2017).…”
mentioning
confidence: 99%